Legal Analysis and Protection of Victims of Domestic Violence - Wahid, Andi Ismayana; Jamaluddin, Jamaluddin; Herman, Herman; Mahka, Muh. Fachrur Razy (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
Abstract Domestic Violence (DV) is one of the most common forms of human rights violations in Indonesia and has a direct impact on the physical, psychological, social, and economic conditions of victims. Law Number 23 of 2004 concerning the Elimination of Domestic Violence affirms that domestic violence is a criminal act and provides a legal basis for the state to carry out prevention, action, and protection of victims. This study aims to analyze the legal regulations regarding domestic violence and evaluate the effectiveness of victim protection within the framework of positive Indonesian law. The study uses a normative juridical method with a statutory approach (statute approach), a conceptual approach (conceptual approach), and a case approach (case approach). Data were obtained through analysis of legislation and legal literature. The results of the study indicate that forms of domestic violence include physical, psychological, sexual violence, and neglect, with women and children being the most vulnerable groups. Normatively, Law No. 23 of 2004 provides protection instruments in the form of protection orders, legal and psychological assistance, health services, and reporting mechanisms aimed at providing a sense of security for victims. However, its implementation still faces challenges in the form of a patriarchal culture, a lack of understanding among law enforcement officials, limited service facilities, and low public legal literacy. This study concludes that although the legal framework for protecting victims of domestic violence is quite comprehensive, its effective implementation still needs to be strengthened. Recommendations include increasing the capacity of officials, strengthening coordination between service institutions, reformulating policies based on a gender perspective, and developing a protection system that is more responsive to victims' needs. [Kekerasan Dalam Rumah Tangga (KDRT) merupakan salah satu bentuk pelanggaran hak asasi manusia yang paling sering terjadi di Indonesia dan berdampak langsung terhadap kondisi fisik, psikologis, sosial, dan ekonomi korban. Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga menegaskan bahwa KDRT adalah tindak pidana serta memberikan landasan hukum bagi negara dalam melakukan pencegahan, penindakan, dan perlindungan korban. Penelitian ini bertujuan untuk menganalisis pengaturan hukum mengenai KDRT serta mengevaluasi efektivitas perlindungan korban dalam kerangka hukum positif Indonesia. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan kasus (case approach). Data diperoleh melalui analisis peraturan perundang-undangan, literatur hukum, Hasil penelitian menunjukkan bahwa bentuk KDRT meliputi kekerasan fisik, psikis, seksual, dan penelantaran, dengan perempuan dan anak sebagai kelompok paling rentan. Secara normatif, UU No. 23 Tahun 2004 telah menyediakan instrumen perlindungan berupa perintah perlindungan, pendampingan hukum dan psikologis, layanan kesehatan, serta mekanisme pelaporan yang diarahkan untuk memberikan rasa aman bagi korban. Namun implementasinya masih menghadapi tantangan berupa budaya patriarki, kurangnya pemahaman aparat penegak hukum, keterbatasan fasilitas layanan, serta rendahnya literasi hukum masyarakat. Penelitian ini menyimpulkan bahwa meskipun kerangka hukum mengenai perlindungan korban KDRT sudah cukup komprehensif, efektivitas pelaksanaannya masih perlu diperkuat. Rekomendasi yang diajukan meliputi peningkatan kapasitas aparat, penguatan koordinasi antar lembaga layanan, reformulasi kebijakan berbasis perspektif gender, serta pengembangan sistem perlindungan yang lebih responsif terhadap kebutuhan korban.] Keywords: domestic violence, victim protection, legal analysis, Domestic Violence Law, human rights.]